2022
DOI: 10.3390/molecules27051594
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation on Competitive Adsorption Differences of Gas with Different Pore Sizes in Coal

Abstract: Micropores are the primary sites for methane occurrence in coal. Studying the regularity of methane occurrence in micropores is significant for targeted displacement and other yield-increasing measures in the future. This study used simplified graphene sheets as pore walls to construct coal-structural models with pore sizes of 1 nm, 2 nm, and 4 nm. Based on the Grand Canonical Monte Carlo (GCMC) and molecular dynamics theory, we simulated the adsorption characteristics of methane in pores of different sizes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…4 . The CO 2 absolute adsorption under 10 MPa is 8.6 mmol/g, 7.4 mmol/g, and 6.7 mmol/g at respectively 308 K, 338 K, and 368 K. This computed adsorption amount is in line with the observations by Raza, Ottiger, and other studies 35 37 , 39 , 40 , presenting 10.5 mmol/g in simulation, and 9.0 mmol/g by simulation under the same conditions. Figure 4 a–c demonstrate a decreasing trend in CO 2 adsorption amount with increasing temperature in all directions.…”
Section: Resultssupporting
confidence: 90%
“…4 . The CO 2 absolute adsorption under 10 MPa is 8.6 mmol/g, 7.4 mmol/g, and 6.7 mmol/g at respectively 308 K, 338 K, and 368 K. This computed adsorption amount is in line with the observations by Raza, Ottiger, and other studies 35 37 , 39 , 40 , presenting 10.5 mmol/g in simulation, and 9.0 mmol/g by simulation under the same conditions. Figure 4 a–c demonstrate a decreasing trend in CO 2 adsorption amount with increasing temperature in all directions.…”
Section: Resultssupporting
confidence: 90%
“…Meng et al explored the adsorption mechanism of coal molecules for CH 4 using the GCMC method and density functional theory and found that compared with oxygen-containing functional groups, molecules with aromatic structures within coal molecules showed a greater adsorption capacity for CH 4 . To investigate the adsorption characteristics of coal under different pore size conditions, Han and Mosher et al , used the vacuum layer thickness of the slit model to describe the pore size conditions of coal and applied GCMC and molecular dynamics theories to simulate the adsorption of coal with different pore sizes for CH 4. . Compared with the experimental test, computer simulation of the macromolecular structure can not only provide information that is difficult to measure through experiments but also reduce the experimental costs and provide a better understanding of the mechanism of interaction of substances in the chemical system.…”
Section: Introductionmentioning
confidence: 99%